2012
DOI: 10.1111/j.1472-765x.2011.03191.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wilting and molasses addition on fermentation and bacterial community in guinea grass silage

Abstract: Aims:  Acetic acid is considered an important preservative in tropical grass ensiling. The objective of the current experiments was to follow the ensiling fermentation of low dry matter (DM) tropical grass as a model to study changes in bacterial communities during acetic acid fermentation. Methods and Results:  Direct‐cut and wilted guinea grass silage was prepared with and without molasses. A high acetic acid level was observed during the fermentation of direct‐cut silage, and long storage increased the buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
56
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 20 publications
15
56
0
3
Order By: Relevance
“…In the present study, the addition of molasses alone enhanced lactic acid fermentation, declining pH. The rapid and vigorous LA accumulation could depress the proteolysis and activity of clostridia or other undesirable bacteria (NISHINO et al, 2012). This is consistent with the lower AA, PA, BA and ammonia N concentration observed in the silages with molasses in the study.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, the addition of molasses alone enhanced lactic acid fermentation, declining pH. The rapid and vigorous LA accumulation could depress the proteolysis and activity of clostridia or other undesirable bacteria (NISHINO et al, 2012). This is consistent with the lower AA, PA, BA and ammonia N concentration observed in the silages with molasses in the study.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, higher BC value in direct-cut A4 alfalfa could partly contribute to the higher pH in direct-cut A4 silage than in the other three cultivars. Nishino et al (2012) suggested that Lactobacillus plantarum was involved in the increase in acetic acid content with prolonged ensiling, because L. plantarum can metabolise lactic acid to acetic acid under sugardeficient conditions. The same metabolic process could have occurred in the case of direct-cut silage because of prolonged ensiling.…”
Section: Discussionmentioning
confidence: 99%
“…Ensilage under farm conditions is not a completely controlled process, because various factors can influence the ensiling process, such as plant species, method of ensiling, climate and DM content (Monteiro et al 1998;Namihira et al 2010;Nishino et al 2012). For the preparation of well-preserved silage, rapid development of the lactic acid fermentation is necessary to reduce the pH and inhibit the growth of inefficient and spoilage microorganisms such as clostridia, enterobacteria, yeast and moulds, which can cause degradation of plant material and/or production of undesirable metabolites (McDonald et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge would be to make ensiling of grass feasible by increasing the growth rates of lactic acid bacteria, dropping silage pH, and enhancing fermentation (Keady and Kiely, 1998;McDonald and Henderson, 1962;Nishino et al, 2012;Chen et al, 2016). If possible, this would configure alternative usage of a potentially pollutant byproduct from biofuel production.…”
Section: Introductionmentioning
confidence: 99%